Implementasi Internet of Things (IoT) dalam Pengelolaan Tempat Sampah Pintar - Musyarrofah; Ulfatun Hasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Abstrak Saat ini kita sedang mengalami Revolusi Industri 4.0 yang memperkenalkan teknologi digital dalam berbagai aspek kehidupan. Salah satu dampak positif dari revolusi ini adalah konsep Internet of Things (IoT) yang memungkinkan otomatisasi dalam aktivitas sehari-hari. Pondok pesantren Al-Ibrahimy di desa Sentol Daya, Pragaan sedang menghadapi masalah kebersihan akibat perilaku membuang sampah sembarangan oleh santri dan masyarakat sekitar. Untuk mengatasi masalah ini, kami mengembangkan tempat sampah pintar dengan menggunakan sensor ultrasonic HC-SR04 dan mesin servo untuk otomatisasi. Kami juga memanfaatkan Arduino Uno dan bahasa pemrograman C++. Melalui serangkaian eksperimen dan pengujian, kami berhasil menciptakan tempat sampah pintar yang membantu pengelolaan sampah sehari-hari. Kata Kunci: Internet of Things, Tempat Sampah Pintar, Otomatisasi —————————————————————————————————- Abstract We are currently facing the all-digital 4.0 revolution, all aspects of human life have been assisted or replaced by the presence of technology. It is not spared from the implementation of various forms of innovation that aim an autoymation. The Internet of Things (IoT) is an automation concept that connects internet and human daily activities in order that easier and more efficient. Al-Ibrahimy is one of the Islamic boarding schools located in Sentol Daya village, Pragaan, which is densely populated with islamic boarding school communities. Not a few social problems arise, including hygiene problems. The bad habits of students and community around the islamic boarding school in terms of littering lead to the accumulation of garbage that is not managed properly. Those problems can be handled by implementing the Internet of Things in smart trash can automation. This implementation is using several sensor components in it, the HC-SR04 ultrasonic sensor functions to detect objects so that it will open the trash can automatically, besides it also as a detector of the amount capacity of the trash volume can fill. In addition, a Servo machine is used which is tasked with pulling and closing the lid automatically. Arduino Uno application which functions to assemble the framework using the C++ programming language. In this case, the method used is experimentation and design. Keyword: Internet of Things, Smart Trash Can, Automation